Hereditary ATTR amyloidosis: a single-institution experience with 266 patients. (June 2015) - Swiecicki, Paul L.; Zhen, David B.; Mauermann, Michelle L.; Kyle, Robert A.; Zeldenrust, Steven R.; Grogan, Martha; Dispenzieri, Angela; Gertz, Morie A.
Abstract Background: Hereditary transthyretin amyloidosis (ATTR amyloidosis) is a rare, clinically heterogeneous disease due to heritable mutations that lead to misfolding of a precursor protein and multisystem disease. This study sought to define the clinical characteristics, distribution of mutations and phenotypic presentation of patients presenting to our center with hereditary ATTR amyloidosis. Methods: With institutional review board approval, the study retrospectively identified patients who had hereditary ATTR amyloidosis and presented to Mayo Clinic in Rochester, Minnesota, from 1 January 1970, to 29 January 2013. Results: Of the 266 patients with the diagnosis of hereditary ATTR amyloidosis, a pathogenic mutation was identified in 206; the most common mutation was Thr60Ala (68 patients [25%]). Median age at diagnosis was 63.3 years; median survival after diagnosis was 56.8 months (10th–90th percentile, 16.0–297.9). On multivariate analysis, age at diagnosis (risk ratio, 15.65; p < 0.0001), Thr60Ala mutation (risk ratio, 1.52; p = 0.04), Val122Ile mutation (risk ratio, 2.83; p = 0.003), peripheral neuropathy (risk ratio, 1.69; p = 0.013) and weight loss (risk ratio, 1.81; p = 0.002) were risk factors for death. Conclusion: Our data characterize the features of hereditary ATTR amyloidosis in a large cohort, demonstrate the heterogeneity among mutations and support the need to better characterize the clinical progression of individual mutations.